Potential Agglomeration of Small Food Industry in Palembang, South Sumatra Indonesia - Mukhlis, Mukhlis; Robiani, Bernadette; Atiyatna, Dirta Pratama (International Journal of Economics and Financial Issues, 2021)
The pattern of the spread of small food industries in Palembang show has led to the establishment of concentration patterns or clusters. This is evident from the grouping type of food industries in certain regions of the city of Palembang. The pattern of industrial activity concentration is spatially often identified with the agglomeration. It is, therefore, necessary to study the level of concentration and agglomeration force for small food industries. The population in this study was small food industries scattered throughout the districts in the city of Palembang. The analytical tool used Herfindahl index, locational Gini index, and the Agglomeration Strength Index. The results showed industrial concentration is highest in the district food Ilir Timur II at 1.4177 with labor contribution of 4.75 percent. Rated power at small industrial agglomeration in Palembang foods obtained at 0.03042, with a specialization level of 0.03036. Overall there are 488 units of small food industry businesses in Palembang and 21.7 percent are in the district of East Ilir II predominantly small soft drink industry with a total production amounting to Rp. 11,779,574. This suggests that small soft drink industry potential for development because it has a fairly wide market prospect and raw materials are relatively easy to obtain, although the potential for agglomeration is still relatively weak. Therefore, developing soft drink industry needs to consider the use of a cluster-based industrial strategy which is based on industry specialization driven by the occurrence of agglomeration in an effort to develop a competitive advantage in the face of competition in the free market era. Keywords: Spatial Concentration, Agglomeration, Herfindahl index, locational Gini index, Agglomeration Strength Index JEL Classification: L66 DOI: https://doi.org/10.32479/ijefi.11300